Optimization analysis of carbon emission rights allocation based on energy justice—The case of China. (20th November 2018) - Fang, Guochang; Liu, Menghe; Tian, Lixin; Fu, Min; Zhang, Yue
Abstract: Carbon emission rights allocation affects the effective operation of carbon trading system, and then the achievement of energy saving and emissions reduction objectives. Reasonable allocation scheme should meet the principle of justice. Carbon emission rights allocation based on energy justice is a novel and worth discussing subject. This paper explores the optimization of carbon emission rights allocation based on energy justice. The justice-based model is built with the aid of Gini coefficient. The way to optimize allocation scheme with constraints of population, ecological productive land, fossil energy resources and GDP is discussed. Results show that fossil energy resources and ecological productive land play more important role in the allocation. The prime example is Inner Mongolia, its quota percentage change reaches up to 150.01%. As the GDP and population growth rate are fixed in a given interval, the quota allocation in eastern China shows some interesting results. When the GDP growth rate is 6.25%, the quotas of eastern China will not change with varying population growth rate. The allocation will enter a relative stable stage as the population growth rate is greater than or equal to 6.4‰. These results can provide China with experience to deal with the new problem appeared in carbon trading system like two-children policy and the new normal of economic growth. Highlights: Energy justice-based carbon emission allocation with multiple constraints is explored. Provincial allocation results in China are related to location-related factors. Two-children policy has effect on optimal allocation results in eastern China. The critical values of population and economic growth rate in this model are found.